Blinded Ultrasound Examination of the Subscapularis Following Anatomic Shoulder Arthroplasty. (February 2019) - O'Malley, Michael P; Kia, Cameron; Dukas, Alex G; Cote, Mark; Stock, Harlan; Savoy, Lawrence; Tinsley, Brian A; Alaee, Farhang; Mazzocca, Augustus D; Shea, Kevin P
Background: The subscapularis tendon is commonly released during shoulder arthroplasty, and its integrity and repair postoperatively have been shown important to help maximize patient function. However, diagnosing subscapular tendon failure can be difficult with magnetic resonance imaging secondary to metal artifact as well as very costly. Purpose: The purpose of this study was to assess the utility of ultrasound imaging in evaluating subscapularis integrity at specific time points following shoulder arthroplasty, in a blinded fashion. Secondarily, we report on the correlation between the condition of the subscapularis and quality-of-life outcome measures. Study Design: Prospective case series. Methods: Ultrasounds were completed preoperatively and postoperatively at 1 week as well as at 1, 3, and 6 months. Each was read by a single musculoskeletal radiologist and categorized as "intact, " "torn, " or "unclear." Clinical outcome was evaluated using the Western Ontario Osteoarthritis Shoulder (WOOS) index at these same time points. Results: The final study group consisted of 35 procedures in 33 patients (19 females and 14 males, mean age 66 ± 9 years). Three patients had postoperative subscapularis failures that were confirmed in the operating room at the time of repair. Of 24 sonographs categorized as "unclear" in the postoperative period, the majority (n = 12, 50%) were taken at 1 week. Compared to preoperative scores, patients had lower WOOS scores at 1, 3, and 6 months postoperatively ( P < .001). Correlation analysis did not reveal an association between the ultrasound readings and the WOOS scores postoperatively. Conclusion: The utility of ultrasound examination of the subscapularis tendon following shoulder arthroplasty is limited by timing and may be most useful when used by the physician within clinical context. Significant improvement was noted in disease-specific quality-of-life scores regardless of the status of the subscapularis tendon as read on ultrasound.